Results of oral litholysis with ursodeoxycholic acid in a patient with cholesterol cholecystolithiasis - Pavel V. Seliverstov; Valerii G. Radchenko; Olga P. Dudanova; Nadezhda A. Larina; Irina V. Kurbatova; Anastasia А. Shipovskaya (Терапевтический архив)
Materials and methods. The study involved 58 patients with cholelithiasis: 56.9% – with stones and 43.1% – with biliary sludge; women – 60.3%, men – 39.7%, the average age of the examined was 60.5±11.6 years. The asymptomatic course was in 46.6% of patients, and the pain syndrome was registered in 53.4%. The diagnosis was verified based on the results of ultrasound examination of the abdominal organs, the X-ray transparency of the concretions was confirmed by X-ray examination and computed tomography. Single stones were found in 63.6% of the patient and double stones in 36.4% of patients. The size of the concretions was 7.71±4.15 mm (3–15 mm). All patients had from 3 to 5 signs of metabolic syndrome. Patients took UDCA at a dose of 10–13 mg / kg for 6–24 months.